Effects of dry cupping on exercise, autonomic activity and sleep in baseball players during preseason and in-season conditioning. - Chien-Liang Chen; Jing-Shia Tang (PLoS ONE)
Background Cupping therapy has been shown to alleviate muscle fatigue, sustain exercise capacity, enhance post-exercise recovery of autonomic activity, and improves sleep quality. However, variations in athletes' training intensity, competition pressure, and fatigue levels throughout a sports season remain underexplored. Few studies have investigated whether the health benefits of cupping differ across various phases of a sports season. This study aimed to examine the effects of short-term cupping on athletes during preseason conditioning (PSC) and in-season conditioning (ISC). Methods Forty university baseball players were recruited and randomly assigned to either the cupping (dry cupping at - 400 mmHg) or sham (dry cupping at - 100 mmHg) group. Cupping was applied to the upper back and shoulders for 15 minutes, twice a week for 8 consecutive weeks (4 weeks each during PSC and ISC). Results Cupping had no significant effect on upper-extremity function during either PSC or ISC. Exercise tests during PSC and ISC revealed no postintervention changes in peak power, peak oxygen consumption, or anaerobic threshold. However, cupping during PSC improved postexercise recovery of low-frequency power (LF; P = .013; a component of heart rate variability) and that during ISC improved recovery of the LF/high-frequency power ratio (P = .004) and LF% (P = .037). Additionally, cupping during PSC notably enhanced daytime function, as measured by the Pittsburgh sleep quality index (P = .026). Conclusions The benefits of cupping therapy vary between PSC and ISC. Cupping during PSC and ISC notably improved the postexercise recovery of autonomic and sympathetic activities, respectively. However, improvements in sleep quality were only observed during PSC.